Characteristics of Growol Dried Noodles With Addition of Nuts Sprout Flour Substitution - Ichlasia Ainul Fitri; Bayu Kanetro; Wisnu Eka Baskhara; Basuki Wicaksono; Ayu Pratiwi Nurhidayati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Growol wet noodles are a food product made from cassava which is processed into growol flour as the main ingredient, as well as additional ingredients in the form of green bean sprout flour and cowpea. Growol flour is made with the principle of cassava which is fermented spontaneously for 3 days then dried. While sprout flour is made by germinating beans for 48 hours then dried. The purpose of this study was to determine the effect of adding mung bean and tolo bean sprouts on the physical, chemical characteristics and level of preference of growol wet noodles that meet the requirements and are liked by panelists. The experimental design of this study used a Completely Randomized Design (CRD) with two factors, namely the type of sprouts (mung bean sprouts and tolo bean sprouts) and the concentration of added sprouts (0%, 20%, and 30%). Physical analysis includes color, cooking loss, and water absorption. Chemical analysis includes water content, ash content, protein, fat, carbohydrates, antioxidants and flavonoids. Organoleptic properties were tested based on the level of preference. The data obtained were then subjected to statistical analysis with a 95% confidence level using the One Way Anova method. The results of the research show that the best growol wet noodles based on physical, chemical and organoleptic characteristics are wet noodles with the addition of 30% cowpea sprout flour which has physical characteristics such as lightness intensity 42,42, reddness -1.43, yellowness 13,97, cooking loss 1.21% and water absorption capacity 92.29. Chemical characteristics such as water content 57,75%(wk), ash content 1.11%(wk), protein content 7.85%(wk), fat content 0.88% (wk), carbohydrates 32,41%, antioxidant activity 16.43%RSA, fenolik 0,45 mg GAE/g, and flavonoids 4.73 mgQE/g.